The effect of using kefir grains and mesenchymal stem cells in LPS-induced Alzheimer’s disease neuroinflammatory model - Anwar, Mai M.; M. Ali, Ola S.; Ahmed R., Laila; A. M., Badawi; Eltablawy, Nadia A. (Revista eNeurobiología, 2019)
La enfermedad de Alzheimer (EA) se caracteriza por una acumulación severa de placas amiloides y ovillos neurofibrilares acompañados de disfunciones cognitivas severas que conducen a cambios importantes que afectan la calidad del patrón de vida diaria del paciente. El objetivo del presente estudio es investigar los efectos de la administración de células madre mesenquimales (MSC) y/o granos de kéfir de leche en el modelo de tipo neuroinflamatorio de EA inducida por LPS de manera alternativa. Se observó que una elevación significativa del perfil lipídico y el estrés oxidativo estaban relacionados con EA de tipo neuroinflamatoria inducida con LPS. La expresión del gen BDNF, Bcl-2 y seladin-1 también se redujo significativamente en ratas con EA, mientras que la expresión relativa de Bax aumentó significativamente. La administración de granos de kéfir de leche y/o MSC suprimió los inconvenientes de la EA incluyendo cambios de comportamiento y memoria. Conclusión: La administración previa y la coadministración de granos de kéfir de leche con MSC pueden actuar como un neuromodulador activo que atenúa el proceso inflamatorio patológico subyacente que acompaña a la EA, lo que resulta en la progresión de daños en el tejido cerebral. Abstract: Alzheimer’s disease (AD) is characterized by severe accumulation of amyloid plaques and neurofibrillary tangles accompanied with cognitive dysfunction leading to major changes affecting the quality of patient daily life pattern. Objective: To investigate the effect of MSCs and/or milk kefir grains in LPS –induced AD in female albino rats in alternating manner. Materials and Methods: Sixty female albino rats were divided into equal six groups (ten rats each): group 1: healthy control; group 2: LPS-induced AD; group 3: LPS-induced AD rats received single intravenous injection of MSCs; group 4: LPS-induced AD rats received oral milk kefir; group 5: LPS-induced AD rats received a single intravenous injection of MSCs with a daily milk kefir grain administration for a month; group 6: Rats received kefir for one week prior to the induction of AD followed by a single intravenous injection of MSCs with a daily milk kefir grain administration for a month. AD was assessed by T maze behavioural test month after induction. Brain tissue was collected for monitoring BDNF, Bax, Bcl-2 and seladin-1 gene expression with the measurement of TNF-α, IL-10 and tissue cholesterol. Plasma lipid profile, GSH and MDA were also determined. Results: Revealed that significant elevation of lipid profile and oxidative stress in association with LPS-induction. BDNF, Bcl-2 and seladin-1 gene expression were significantly reduced in AD while Bax mRNA gene was significantly increased. Administration of kefir and /or MSCs suppressed LPS –induced AD. Conclusion: The pre and co-administration of kefir with MSCs could act as a potent modulator attenuating the underling pathological inflammatory process accompanying AD which results in the progression of brain damage. Keywords: Alzheimer's disease; MSCs; kefir grains; LPS; Bax; BDNF; Seladin-1.